Computational surgery and dual training : computing, robotics and imaging - Bass, Barbara Lee; Berceli, Scott; Collet, Christophe; Cerveri, Pietro; Garbey, Marc; Garbey, Marc (Springer New York, 2014)
This critical volume focuses on the use of medical imaging, medical robotics, simulation, and information technology in surgery. It offers a road map for computational surgery success,  discusses the computer-assisted management of disease and surgery, and provides a rational for image processing and diagnostic. This book also presents some advances on image-driven intervention and robotics, as well as evaluates models and simulations for a broad spectrum of cancers as well as cardiovascular, neurological, and bone diseases. Training and performance analysis in surgery assisted by robotic systems is also covered. This book also: ·         Provides a comprehensive overview of the use of computational surgery and disease management ·         Discusses the design and use of medical robotic tools for orthopedic surgery, endoscopic surgery, and prostate surgery ·         Provides practical examples and case studies in the areas of image processing, virtual surgery, and simulation training Computational Surgery and Dual Training: Computing, Robotics and Imaging is an ideal book for graduate students and professionals in the area of bioengineering, computational science, computational medicine, and medical residents in surgery.